Regulation of inflationary processes in the conditions of open economy (on the example of economy of the Republic of Tajikistan) - M. M. Ahmedova (Статистика и экономика, 2019)
The  main  objective of this study  is to identify  the characteristics  of methods  for regulating inflation  processes in an  open  economy.  In this regard, the article discusses in detail such issues as, features of inflationary  processes in an open economy, the specifics of the impact of external  factors on the level of inflation.  On  the example  of the economy of the Republic of Tajikistan, the peculiarities of the influence of the dynamics  of the exchange  rate and  foreign trade factor on the inflation rate are considered,  the main factors influencing the dynamics  of the national  currency exchange  rate are identified,  the problem of regulating inflation tendencies in conditions of high import dependence  is studied.The  theoretical  basis  for  this  study  was  the  work  of  foreign  and domestic scientists on the problems of inflation  in an open economy, the impact  of the exchange  rate on inflationary  processes, and  the anti-inflationary monetary  policy  under  conditions  of  high  import dependence.  Statistical  data of the National  Bank  of the Republic of Tajikistan website - www.nbt.tj and the Statistical Agency under the President of the Republic of Tajikistan - www.stat.tj for 2000-2019 were used as an information  database.Results.  The  main  factors  of  inflation  in  an  open  economy  are identified.  The mechanism  of direct and indirect influence  of foreign economic factors, in particular the exchange rate on inflationary processes, is investigated. The main factors of inflation and the mechanism  of their influence  on the example  of the Republic of Tajikistan are investigated.  The significant influence of external factors (imports,  cash flow,  exchange  rate,  dynamics  of the Russian  ruble) on inflationary  processes and economic development  of the Republic of Tajikistan has been  revealed.  The  study  shows  that  import is a factor  that  holds  back  inflationary  trends  in  the  country,  external cash  flows  form  domestic  demand, influence  the  dynamics  of  the Somoni rate, and thereby affect the inflation rate. The significance of the Somoni  exchange  rate in regulating inflation  processes has been determined.  Significant influence of external factors on the formation of the Somoni  exchange  rate also was  revealed.  Based  on the correlation  and  regression analysis,  a close relationship  is established between  the dynamics  of the Tajik  Somoni  and  the Russian  ruble. The  article studies  the peculiarity  of the use of monetary  policy in order to stimulate  domestic production and export.The  results of the study show that in the conditions of the Republic of Tajikistan, foreign economic  factors,  in particular  the  exchange rate, largely determine inflationary trends. On this basis, an objective need arises to maintain  the stability of the national currency in order to curb inflation  and  ensure the stability of economic  development. The study showed that the dynamics  of the exchange rate of Somoni largely determined  by external than internal factors. For this reason, the presence of a significant effect of the exchange rate on inflationary trends in the long term may lead to undesirable consequences that are associated with  the problem of regulating the exchange  rate.